Investigasi pengaruh pengenceran sampel madu pada proses klasifikasi madu menggunakan uv spectroscopy dan kemometrika [Investigation on the influence of dilution of honey samples for honey classification using uv spectroscopy and chemometrics] - Diding Suhandy; Meinilwita Yulia; Kusumiyati Kusumiyati; Siti Suharyatun; Sri Waluyo (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2021)
One form of honey adulteration is label adulteration for some premium honey such as uniflora honey from the honeybee species Trigona sp. One of the analytical methods that are currently developing and have the potential to perform the classification of premium honey in Indonesia is the UV spectroscopy method. In this study, an investigation was carried out on the effect of dilution on the performance of UV spectroscopy in the process of classifying Indonesian honey with different honeybees. A total of 4 types of honey samples with 10 samples each were used in this study. The honey sample was then diluted using distilled water. Each type of honey was given two dilution treatments, namely 1:20 (volume: volume) dilution of 5 samples and 1:40 (volume: volume) dilution of 5 samples. Spectral data were taken using a UV-visible spectrometer with a wavelength of 190-1100 nm (Genesys™ 10S UV-Vis, Thermo Scientific, USA) using the transmittance mode. The results of spectra analysis generally show that the sample with a 1:20 dilution has a higher absorbance intensity for both the original and modified spectra. The PCA results for each dilution showed that the honey samples could be separated into four different clusters for both 1:20 and 1:40 dilutions. The results of PCA analysis using all samples showed that the honey samples were classified into eight different clusters showing a significant effect of differences in honey sample dilution on the classification process of honey samples based on differences in the types of honeybees.